Unimaginable imagination and political commitment. A survey of the introduction and presence of the literature of the Latin American boom in Sweden in 1960–1990 - Ingela Johansson (Moderna Språk)
This study investigates the publication and reception of the Latin American boom literature in Sweden from 1960 to 1990, focusing on Julio Cortázar, Carlos Fuentes, Gabriel García Márquez and Mario Vargas Llosa. It analyses the extent of Swedish translations of their works and the type and amount of attention they received in the Swedish press. Using a bibliometric approach for the translations, and analysing press material on the authors from the evening papers Aftonbladet and Expressen, the study found that 258 of the 532 works translated from Spanish to Swedish during the investigated period were Latin American, with 52 (20%) by the feautured authors. The press material reveals that García Márquez was the most covered, especially around his 1982 Nobel Prize, and the assessment of his literature and public persona was generally positive. Fuentes received significant attention in the 1980s and was also favourably regarded. Vargas Llosa was introduced early on to the Swedish readership, but his literary work and political engagement elicited mixed reactions. Cortázar received the least press coverage, correlating with fewer translations and less public attention.